The growth, pilodyn penetration, and wood properties of 12 Neolamarckia cadamba provenances at 42 months old - Nelly Anna; Supriyanto; Lina Karlinasari; Dede J Sudrajat; Iskandar Z Siregar (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Anna N, Supriyanto, Karlinasari L, Sudrajat DJ, Siregar IZ. 2020. The growth, pilodyn penetration, and wood properties of 12 Neolamarckia cadamba provenances at 42 months old. Biodiversitas 21: 1091-1100. Jabon (Neolamarckia cadamba (Roxb) Bosser) is a potential tree species for the development of plantation forests and community forests to supply timber demands. Information on the growth characteristics and wood properties of N. cadamba is important for the present and future development, yet. Those data is not available. This study aimed to assess the variations on growth (height, diameter), pilodyn (Pilodyn®) penetration, and physical properties of wood from core sample; and characterize the wood properties of 12 N. cadamba provenances at Parung Panjang, Bogor. The assessment of growth characteristics, pilodyn penetration, and physical properties of wood from core sample was carried out through census (1030 trees) on all provenance (using non-destructive method). The wood properties analysis was carried out using destructive method to one sample for each of the 12 N. cadamba provenances. Growth characteristics observed were the height (numerical scale pole), diameter (calipers), and pilodyn penetration. Meanwhile, the wood properties consisted of wood density, specific gravity, moisture content, fiber length (light microscope), MFA (x-ray diffraction), MOE, and MOR. The results showed that the correlation between the height and moisture content with pilodyn penetration was weak and positive, while the correlation between diameter, wood density, and specific gravity was weak and negative. The result of non-destructive test showed that Gowa provenance is superior. The results of destructive tests to investigate the wood properties of the twelve provenances showed that Batu Licin provenance is superior in terms of specific gravity and MOE, while Gowa provenance is superior in terms of MOR and fiber length. The results of the wood properties (i.e. density, specific gravity, moisture content, MOE, MOR, MFA, and fiber length) of the 12 N. cadamba provenances showed that the woods can be potentially used as non-structural materials only.